Application of bioactive glasses in various dental fields - Nazanin Jafari; Mina Seyed Habashi; Alireza Hashemi; Reza Shirazi; Nader Tanideh; Amin Tamadon (Biomaterials Research, 2022)
Abstract Bioactive glasses are a group of bioceramic materials that have extensive clinical applications. Their properties such as high biocompatibility, antimicrobial features, and bioactivity in the internal environment of the body have made them useful biomaterials in various fields of medicine and dentistry. There is a great variation in the main composition of these glasses and some of them whose medical usage has been approved by the US Food and Drug Administration (FDA) are called Bioglass. Bioactive glasses have appropriate biocompatibility with the body and they are similar to bone hydroxyapatite in terms of calcium and phosphate contents. Bioactive glasses are applied in different branches of dentistry like periodontics, orthodontics, endodontics, oral and maxillofacial surgery, esthetic and restorative dentistry. Also, some dental and oral care products have bioactive glasses in their compositions. Bioactive glasses have been used as dental implants in the human body in order to repair and replace damaged bones. Other applications of bioactive glasses in dentistry include their usage in periodontal disease, root canal treatments, maxillofacial surgeries, dental restorations, air abrasions, dental adhesives, enamel remineralization, and dentin hypersensitivity. Since the use of bioactive glasses in dentistry is widespread, there is a need to find methods and extensive resources to supply the required bioactive glasses. Various techniques have been identified for the production of bioactive glasses, and marine sponges have recently been considered as a rich source of it. Marine sponges are widely available and many species have been identified around the world, including the Persian Gulf. Marine sponges, as the simplest group of animals, produce different bioactive compounds that are used in a wide range of medical sciences. Numerous studies have shown the anti-tumor, anti-viral, anti-inflammatory, and antibiotic effects of these compounds. Furthermore, some species of marine sponges due to the mineral contents of their structural skeletons, which are made of biosilica, have been used for extracting bioactive glasses.